2023
DOI: 10.1021/acsnano.2c11691
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Checkpoint Immunotherapy with Biomaterials

Abstract: The immune checkpoint blockade (ICB) therapy has revolutionized the field of cancer treatment, while low response rates and systemic toxicity limit its clinical outcomes. With the rapid advances in nanotechnology and materials science, various types of biomaterials have been developed to maximize therapeutic efficacy while minimizing side effects by increasing tumor antigenicity, reversing immunosuppressive microenvironment, amplifying antitumor immune response, and reducing extratumoral distribution of checkp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 287 publications
1
34
0
Order By: Relevance
“…44 Moreover, it is reported that virus-like particles activate the epitopes and lipid membrane layers on the cells and thus show enhancement in the cellular uptake. 45,46 The results suggested that VSNP are better at connecting with the cells, and potentially more particles are able to interact with the tight junction proteins.…”
Section: Cell Viability and Cellular Uptakementioning
confidence: 99%
“…44 Moreover, it is reported that virus-like particles activate the epitopes and lipid membrane layers on the cells and thus show enhancement in the cellular uptake. 45,46 The results suggested that VSNP are better at connecting with the cells, and potentially more particles are able to interact with the tight junction proteins.…”
Section: Cell Viability and Cellular Uptakementioning
confidence: 99%
“…The advancement of nanomaterials offers a potential strategy for enhancing the effectiveness of ICB therapy . Kataoka et al developed a pH-sensitive epirubicin-loaded micelles (Epi/m) for synergizing the efficacy of anti-PD-1 antibody against PTEN-negative GBM enriched with CSCs (Figure A) .…”
Section: Strategies For Sniping Cscsmentioning
confidence: 99%
“…46,290−292 The advancement of nanomaterials offers a potential strategy for enhancing the effectiveness of ICB therapy. 293 Kataoka et al developed a pH-sensitive epirubicin-loaded micelles (Epi/m) for synergizing the efficacy of anti-PD-1 antibody against PTENnegative GBM enriched with CSCs (Figure 8A). 294 Epi/m exerted its impact by inducing ICD, eradicating immunosuppressive myeloid-derived suppressor cells, and transforming the "cold" GBM TME into a "hot" TME with heightened infiltrating antitumor immune cell (Figure 8B).…”
Section: Strategies For Sniping Cscsmentioning
confidence: 99%
“…Flexible electronics exhibited excellent flexibility, stretchability, and electrical properties endowed them with a wide range of potential applications including flexible robotics, biomedicine, wearable devices, electronic skin, and artificial intelligence. [1][2][3][4] Among them, the flexible sensor was one of the core components of electronic devices. [5,6] The flexible conductive materials used to fabricate sensors acquire information about the outside world by detecting externally applied stimuli and converting them into electrical signals.…”
Section: Introductionmentioning
confidence: 99%